2009
DOI: 10.1007/s11033-009-9699-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel SNPs of the bovine GAD1/gad67 gene and their association with growth traits in three native Chinese cattle breeds

Abstract: In this study, polymorphism in the exon 1, 2, 3, 4 and 5 of bovine GAD1 gene was detected by PCR-SSCP and DNA sequencing methods in 726 individuals from three Chinese cattle breeds. Two haplotypes (T and C) and three observed genotypes (TT, TC, and CC) were detected. The result of DNA sequence showed one mutations (T12345C) by comparisons with NC_007300: g.12345T>C. The mutation was at the exon 3, and was identified a missense mutation Phe (TTT)>Leu (CTT) at position 51 (p.F51L). Polymorphism of the GAD1 gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The greatest differences in the physical phenotypes of these two breeds are their body size and adaptation to different environments. There are many genes that have been reported to be associated with the economic traits of cattle (Li et al, 2010;Pausch et al, 2017;Raza et al, 2018;Sun et al, 2018;Cheng et al, 2020). In particular, genes such as MYLK4 (Zheng et al, 2019), CRTC3 (Wu et al, 2018), LEPR (Guo et al, 2008), and LHX4 (Ren et al, 2010) have been reported to be associated with the growth traits of Chinese cattle breeds.…”
Section: Discussionmentioning
confidence: 99%
“…The greatest differences in the physical phenotypes of these two breeds are their body size and adaptation to different environments. There are many genes that have been reported to be associated with the economic traits of cattle (Li et al, 2010;Pausch et al, 2017;Raza et al, 2018;Sun et al, 2018;Cheng et al, 2020). In particular, genes such as MYLK4 (Zheng et al, 2019), CRTC3 (Wu et al, 2018), LEPR (Guo et al, 2008), and LHX4 (Ren et al, 2010) have been reported to be associated with the growth traits of Chinese cattle breeds.…”
Section: Discussionmentioning
confidence: 99%
“…NEUROD1 is mapped to bovine chromosome 2 near QTLs for RFI, ADG, BW, and REA (Casas et al, 2003;Allais et al, 2010;Li et al, 2010;Martínez et al, 2010;Sherman et al, 2010). Seven candidate genes, including bridging integrator 1 (BIN1), asparagine synthetase domain-containing protein 1 (ASNSD1), and aldehyde oxidase (AOX1) are associated with RFI on bovine chromosome 2 (Karisa et al, 2013), near to SNPs (599C>G, 1008G>A, and 1743T>C) found in NEUROD1.…”
Section: Discussionmentioning
confidence: 99%
“…This gene is located on bovine chromosome 2, near quantitative trait loci (QTLs) for residual feed intake (RFI) (Martínez et al, 2010;Sherman et al, 2010), average daily gain (ADG) (Li et al, 2010), body weight (BW) (Casas et al, 2003), and REA (Allais et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The candidate gene approach is a very effective method to analyze the association between gene polymorphisms and valuable economical traits in farm animals (Rothschild and Soller, 1997). Through the candidate gene approach, studies have been performed on animal reproduction (Chu et al, 2010), growth (Li et al, 2010), and MQTs (Jiao et al, 2010), which will provide more valuable data for further research. To facilitate the Chinese indigenous cattle-breeding program, further molecular genetic information on quantitative trait loci should be collected (Adoligbe et al, 2012).…”
Section: Discussionmentioning
confidence: 99%